The Influence of Principal Leadership and Teacher Professionalism on Teacher Performance at Kandis Public Elementary School, Siak Regency - Irasari, Irasari (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the combined influence of principal leadership and teacher professionalism on the performance of teachers at public elementary schools in Kandis District, Siak Regency. Employing a quantitative approach, the research was conducted at Cluster III Sultan Syarif Kasim II, which comprises four schools: SD 003, SD 006, SD 012, and SD 020. The sample consisted of 45 teachers who had participated in the Teacher Performance Assessment (PKG) program. Data were analyzed using inferential statistical methods. The findings reveal that principal leadership has a significant influence on teacher performance, contributing 39.5%, while teacher professionalism also significantly affects teacher performance, contributing 22.9%. Furthermore, the combined influence of principal leadership and teacher professionalism accounts for 53.3% of the variation in teacher performance, with the remaining 46.7% attributed to other factors.